Psychopharmacologic characteristics of substance dependence - Sağlam, Esra; İ. Uzbay, Tayfun; Beyazyürek, Mansur (Journal of Dependence, 2003)
Dopamin neurotransmission is thought to mediate in large part the psychopharmacology of substance dependence. However, neurotransmission at other receptors in central nervous system (CNS), as GABA, serotonin, and nitric receptors may be involved in regulating neuronal systems in substance dependence. Psychopharmacologic studies in substance dependence show that abuse and reward have common cellular and molecular mechanisms.It is considered that mesocorti-co-limbic dopamin pathway like n.accumbens is the ‘’pleasure center’’ of the brain. Alcohol, opioids, amphetamines, sedative-hypnotics and nicotine all have an impact on this mesolimbic dopaminergic system. Psychotropic drugs that interact with dopamin,se-rotonin,GABA,and norepinephrine systems may be involved in the treatment of substance dependence.Thus, these systems are considered as targets in the development of effective and new drugs. Moreover, inhibitors of nitric oxide synthetase could play a role in the treatment and substance dependence. In this article, we rewieved the related literatures.
Keywords: Substance dependence; psychopharmacology; mechanisms